Carbon adjustment mechanisms: Empirics, design and caveats - Niklas Garnadt; Veronika Grimm; Wolf Heinrich Reuter (Sachverständigenrat zur Begutachtung der Gesamtwirtschaftlichen Entwicklung, 2020)
This article explores the design of Carbon Adjustment Mechanisms based on an analysis of historical data, the existing literature as well as theoretical considerations. In the empirical analysis we quantify territorial emissions as compared to the CO2 footprints for countries within the EU-ETS area and globally, we show which (mostly upstream) industries account for the majority of emissions, and identify how their emissions are imported embedded in final or intermediate products from more downstream industries. In an analysis based on gravity equations, we find evidence for carbon leakage in some emission-intensive industries, but only small overall effects. Based on our own evidence and the current literature, we conclude that - if a Carbon Adjustment Mechanism is to be established - focusing on emissions intensive industries could balance excessive bureaucratic burden and carbon leakage mitigation. To be effective, such a system should also extend to embedded emissions in downstream industries to avoid a shift of imports down the value chain. Concerns with regard to international trade relations could be addressed by not implementing Carbon Adjustment Mechanisms unilaterally, but rather using them as the basis for a cooperative approach to climate protection jointly with the most important trading partners.
Keywords: Q56; Q53; F18; F14; F55; F64; 330; Carbon border adjustment; Carbon leakage; Carbon tax; Climate policy